2021
DOI: 10.1177/00207640211052174
|View full text |Cite
|
Sign up to set email alerts
|

How does the British public understand mental health? A qualitative analysis of open-text responses

Abstract: Background: An individual’s understanding of mental health can influence their attitudes towards those experiencing mental health problems, and also impact their response to any mental health problems they experience. However, what the lay public understand about mental health is not well explored in existing research. Aims: This study aims to gain a deeper insight into what the general public understand by the term ‘mental health problem’. Methods: Data were taken from a large-scale representative sample of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Perkembangan kesehatan mental anak dan remaja dewasa ini dinilai perlu perhatian yang lebih. Beberapa kajian penelitian menemukan bahwa saat ini cenderung terdapat peningkatan kasus kesehatan mental pada usia anak-anak, remaja hingga dewasa (Arnot et al, 2022;Ayuningtyas et al, 2018;Radiani, 2019). Kesehatan mental secara umum didefinisikan sebagai kondisi sesorang yang berkaitan dengan kecemasan, stress dan depresi (Dorsey et al, 2015).…”
Section: Pendahuluanunclassified

Kajian Kesehatan Mental pada Anak-Anak Yatim Piatu

Indra Praekanata,
Komang Sri Yuliastini,
Florina Laurence Zagoto
et al. 2023
pelitapaud
“…Perkembangan kesehatan mental anak dan remaja dewasa ini dinilai perlu perhatian yang lebih. Beberapa kajian penelitian menemukan bahwa saat ini cenderung terdapat peningkatan kasus kesehatan mental pada usia anak-anak, remaja hingga dewasa (Arnot et al, 2022;Ayuningtyas et al, 2018;Radiani, 2019). Kesehatan mental secara umum didefinisikan sebagai kondisi sesorang yang berkaitan dengan kecemasan, stress dan depresi (Dorsey et al, 2015).…”
Section: Pendahuluanunclassified

Kajian Kesehatan Mental pada Anak-Anak Yatim Piatu

Indra Praekanata,
Komang Sri Yuliastini,
Florina Laurence Zagoto
et al. 2023
pelitapaud
“…The results show that this method has high accuracy. Arnot et al (2021) argues that an individual’s experiences and attitudes toward life can affect an individual’s mental health, which in turn affects their perception of the problems they encounter, which in turn affects mental health education issues. It also found that the public is less aware of mental health knowledge and education.…”
Section: Related Workmentioning
confidence: 99%
“…While emotional expressions are made on social media in the real world and in real-time, the patients' demographic and disease characteristics are incomplete or unavailable on these platforms (27,28). Arguably, therefore, it is difficult to capture the full range of nuances in patients' disclosures of their emotional experiences from a single data source, especially concerning women living with BC in China, where cultural norms strongly discourage emotional disclosure (27,32). Use of a single-source method would likely skew results and fail to reflect the target population's comprehensive range of experiences.…”
Section: Introductionmentioning
confidence: 99%